2020
DOI: 10.1136/annrheumdis-2019-216500
|View full text |Cite
|
Sign up to set email alerts
|

GO-DACT: a phase 3b randomised, double-blind, placebo-controlled trial of GOlimumab plus methotrexate (MTX) versus placebo plus MTX in improving DACTylitis in MTX-naive patients with psoriatic arthritis

Abstract: ObjectivesTo assess the efficacy of golimumab in combination with methotrexate (MTX) versus MTX monotherapy in psoriatic arthritis (PsA) dactylitis.MethodsMulticentre, investigator-initiated, randomised, double-blind, placebo-controlled, parallel-design phase 3b trial in 11 Portuguese rheumatology centres. Patients with PsA along with active dactylitis and naive to MTX and biologic disease-modifying antirheumatic drugs (bDMARDs) were randomly assigned to golimumab or placebo, both in combination with MTX. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 30 publications
1
56
0
Order By: Relevance
“…Thus, we included 35 trials in the systematic review. In addition, four trials ( 17 20 ) did not mention the portion of nail involvement or enrolled patients with nail psoriasis, the remaining 31 trials included 17,254 patients with psoriasis, and 10,720 (62.1%) had nail involvement. The flow diagram is shown in Figure 1 , and Supplementary Figure 1 provides the quality assessment for the included trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we included 35 trials in the systematic review. In addition, four trials ( 17 20 ) did not mention the portion of nail involvement or enrolled patients with nail psoriasis, the remaining 31 trials included 17,254 patients with psoriasis, and 10,720 (62.1%) had nail involvement. The flow diagram is shown in Figure 1 , and Supplementary Figure 1 provides the quality assessment for the included trials.…”
Section: Resultsmentioning
confidence: 99%
“…The median improvement in NAPSI score from baseline to weeks 14 and 24 was significantly greater ( P < 0.001) in the golimumab 50 mg group (25, 43%) and the golimumab 50 mg group (33, 54%) compared to that in the placebo group (0, 0%, respectively). Vieira-Sousa et al ( 20 ) evaluated methotrexate monotherapy or combination therapy with golimumab in 44 patients. After 12 weeks of treatment, the medium percentage of reduction in target fingernail NAPSI score (0–8) from baseline for combination therapy was greater than that of methotrexate monotherapy (−2 vs. 0, P = 0.044).…”
Section: Resultsmentioning
confidence: 99%
“…To date there is only one study addressing dactylitis as a primary endpoint, the GO-DACT study, 31 a multicentre, randomized, double-blind, placebo-controlled, phase-3b trial of golimumab plus methotrexate (MTX) versus placebo plus MTX, in MTX-naïve and biologic disease-modifying anti-rheumatic drugs (bDMARDs) naïve patients with PsA and active dactylitis. The primary endpoint was DSS change from baseline to week 24.…”
Section: Current Treatment Strategiesmentioning
confidence: 99%
“…The GO-DACT trial showed that the combination of golimumab plus MTX is associated with significantly greater clinical improvements in dactylitis in comparison with MTX monotherapy. 31 …”
Section: Current Treatment Strategiesmentioning
confidence: 99%
“…107 Of interest, weight loss was observed at 52 weeks, suggesting that APR could have a positive impact on obesity and metabolic syndrome. 108 To date, there is no evidence to demonstrate an impact of APR on structural disease progression: the results from PALACE analysis indicated significant improvements in the 42 Phase IV (EDUCATE) 194 Phase IV (REPArE) 195 Observational study (ADEQUATE 45 Observational study (GO-NICE) 202 Phase IIIb (GO-DACT) 203 Phase III (GOLMEPsA) numbers of swollen and tender joints over 5 years of treatment, that may have been associated with inhibition of disease progression. 104 Nevertheless data from real life studies have recently evidenced that APR is able to induce an early and sustained improvement on ultrasonographic inflammatory status at articular and peri-articular level.…”
Section: Targeted Synthetic Dmardsmentioning
confidence: 99%